Pengaruh Liquiditas, Leverage, Firm Size & Capital Intensity terhadap Profitabilitas pada Perusahaan Sub-Sektor Property & Real Estate yang Terdaftar pada Bursa Efek Indonesia Periode 2018 - 2022 - Febrianti, Ira; Zuwarni, Feggi Rahma; Adisetiawan, R. (Universitas Batanghari Jambi, 2025)
This study aims to analyze the effect of liquidity, leverage, company size, and capital intensity on profitability in property and real estate sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the 2018–2022 period. The population of this study was all property and real estate sub-sector companies, and using a purposive sampling technique, 20 issuers were obtained as research samples. The data used were secondary data from annual financial reports analyzed by multiple linear regression. The results showed that simultaneously, the variables of liquidity, leverage, company size, and capital intensity had a significant effect on profitability. However, partially, liquidity, company size, and capital intensity had a positive but insignificant effect on profitability, while the variable of leverage had a significant negative effect on profitability in property and real estate sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the 2018–2022 period.